Gestión de cobranza morosa en el área de facturación del Hospital III Iquitos - EsSalud, periodo 2019 – 2021 - Donayre Vasquez, Paulo Angel (2023)
The objective of this research was to determine how the management of delinquent collections is carried out in the billing area of Hospital III Iquitos - EsSalud, period 2019 - 2021, with a type of quantitative research of non-experimental design and a type of longitudinal design; the study population will be finite and will be made up of debt reports from the billing area and a survey conducted with 18 workers in the collections area of Hospital III Iquitos – EsSalud, concluded that, Income & delinquency in monetary units of care provided to uninsured users in the periods 2019 to 2021 are not recovered; since it is evident that in 2019 Hospital III Iquitos had a total income of S/ 92,429.52 and a delinquency of S/ 407,563.09, in 2020 it received S/ 83,376.41 with a delinquency of S/ 300, 107.82 and in 2021 it entered S/ 200,763.44 with a delinquency of S/ 459, 170.34, Income & delinquency in monetary units of the care provided to employers in the periods 2019 to 2021 shows that the attention is not recovered; since it is evident that in 2019 Hospital III had income of S/ 29,704.18 with a delinquency of S/ 478,348.75, in 2020 it received S/ 45,146.56 with a delinquency of S/ / 479,354.04 and in 2021 it entered S/ 54,099.56 with a delinquency of S/ 174,826.64.